2006
DOI: 10.3892/ijmm.18.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophins and neurotransmitters in human palatine tonsils: An immunohistochemical and RT-PCR analysis

Abstract: Lymphoid organs are supplied by many nerve endings associated with different kinds of cells and macrophages. The role of these neuromediators on the release of locally active molecules is still unknown. Here we focused our attention on the expression of some neurotrophins (NTs), their high-and low-affinity receptors and several neurotransmitters in human palatine tonsils. Light and electron microscopy immunohistochemistry showed that human tonsillar samples were positive for all analyzed neurotrophins (NGF, BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
2
8
1
Order By: Relevance
“…The density of peripheral sympathetic innervation is governed in large part by target organ expression of neurotrophic factors such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) (Carlson, Albers et al 1995;Kuruvilla, Zweifel et al 2004;Bronzetti, Artico et al 2006). Consistent with the hypothesis that stress increases lymphoid tissue innervation via increased neurotrophic support, we found increased expression of both NGF and BDNF in lymph nodes from animals socialized under unstable conditions.…”
Section: Molecular Mechanismssupporting
confidence: 70%
“…The density of peripheral sympathetic innervation is governed in large part by target organ expression of neurotrophic factors such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) (Carlson, Albers et al 1995;Kuruvilla, Zweifel et al 2004;Bronzetti, Artico et al 2006). Consistent with the hypothesis that stress increases lymphoid tissue innervation via increased neurotrophic support, we found increased expression of both NGF and BDNF in lymph nodes from animals socialized under unstable conditions.…”
Section: Molecular Mechanismssupporting
confidence: 70%
“…The data described above confirmed our previous experimental findings (8)(9)(10)(11), hence improving our knowledge on the role of the neurotrophins in the regulation of the meningeal microenvironment and their direct participation in the neoplastic transformation and cellular survival, both essential aspects of the malignant development.…”
Section: Discussionsupporting
confidence: 77%
“…A definite role of NTs in the dural and leptomeningeal compartments is not well ascertained but a previous study on the expression of mRNAs for NTs revealed high levels of NT3 and NGF in the normal rat dura mater (7). Our observations on the localization and possible roles in different non-neuronal tissues such as lymphoid, lung and prostate (8)(9)(10)(11) encouraged us to persist in our experimental investigations in order to find a possible involvement of NTs in dura mater, both in physiological and pathological conditions (meningiomas).…”
Section: Introductionmentioning
confidence: 99%
“…This raises the possibility that reduced neurotrophin expression following SIV infection might be a consequence of denervation, rather than a cause, since neurotrophins may derive from both immune and neural sources (Kuruvilla, et al, 2004;Bronzetti, et al, 2006;Edling, et al, 2004;Frossard, et al, 2004;Levi-Montalcini, 1987). However, two findings argue against the hypothesis that changes in neurotrophin expression are solely a consequence of denervation.…”
Section: Discussioncontrasting
confidence: 45%
“…Sympathetic neurons express p75 NTR , and TrkA, which binds NGF and NT3 (Reichardt, 2006). BDNF is produced by both sympathetic neurons and target-organ cells including leukocytes (Kuruvilla, et al, 2004;Bronzetti, et al, 2006;Edling, et al, 2004). On sympathetic neurons, which lack Trk B, BDNF acts via p75 NTR to antagonize NGF-mediated support for innervation (Kohn, et al, 1999).…”
Section: Introductionmentioning
confidence: 99%